Victoria, Queen of Great Britain, papers - Victoria, Queen of Great Britain, 1819-1901.
Proclamation (1842 July 16) made at the request of Edward Everett, U.S. ambassador to Great Britain, regarding the town of New Castle, Del.; photocopy of a certificate (1852 January 30) appointing John Cooke commissioner in County Roscommon, Ireland; commission (1853 June 7), signed by the queen and Viscount Henry John Temple Palmerston, appointing John MacDonald a major in the British army; and facsimile of a letter (1892 January 26) from the queen to her subjects expressing her appreciation of their sympathy upon the death of her grandson, Prince Albert Victor, Duke of Clarence and Avondale.
In part, negative photocopy and facsimile.
Queen of Great Britain.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Albert Victor, -- Prince, Duke of Clarence and Avondale, -- 1864-1892.; Cooke, John, -- active 1852.; Everett, Edward, -- 1794-1865.; MacDonald, John, -- active 1853.; Palmerston, Henry John Temple, -- Viscount, -- 1784-1865.; Great Britain. -- Army; Great Britain -- Foreign relations -- United States; Great Britain -- History -- Victoria, 1837-1901.; Ireland -- History -- 19th century; New Castle (Del.) -- History; Roscommon (Ireland : County) -- History; United States -- Foreign relations -- Great Britain; Queens -- Great Britain